Laser deburring process for structured edges on precision moulds. (15th September 2011) - Chang, Wenlong; Luo, Xichun; Ritchie, James M.; Sun, Jining; Mack, Christopher
In this paper a laser deburring process is developed to remove micro burrs generated by micromilling processes in order to obtain high quality micro fluidic injection mould. A two-temperature model (TTM) is used to determine the critical laser machining parameters such as the laser energy density and laser power. The laser deburring experiment is carried on by using an Nd:YAG nanosecond laser source with frequency of 15 Hz and a spot size of 5 μm. The edge quality and the machined surface of micro channels in the micro fluidic mould are measured by a SEM and a white light interferometer. The measurement results show that the micro burrs on the micro channels in the micro fluidic mould have been completely removed. The average surface roughness (Ra) was only 0.114 μm after the laser deburring process. Therefore, laser deburring process cannot only remove micro burrs on the micro fluidic channel but also help to achieve good surface finish on the mould.